An Analysis of the Impact of Investment on Economic Growth in Zimbabwe - Chidoko, Clainos; Sachirarwe, Innocent (Review of Knowledge Economy, 2015)
The study seeks to find out the impact of investment on economic growth from 1980 to 2013. The model used is a linear function. It has been discovered that investment positively affect economic growth in Zimbabwe. It is recommended that the investment authorities should check and monitor the magnitude of the contribution made by investment in Zimbabwe to adequately provide investment incentives to those with the resources to do so.